2014
DOI: 10.1111/jopy.12128
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents, Consequences, and Mechanisms: On the Longitudinal Interplay Between Academic Self‐Enhancement and Psychological Adjustment

Abstract: We investigated the reciprocal associations between academic self-enhancement and key indicators of intra- and interpersonal adjustment as well as the role of self-esteem as a mediator. This longitudinal study involved three assessments in a sample of 709 German children and adolescents (Mage  = 11.83; 54% female) over the course of one academic year. We assessed self-reported subjective well-being as an indicator of intrapersonal adjustment and peer-reported popularity as an indicator of interpersonal adjustm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 71 publications
1
49
0
Order By: Relevance
“…We tested first whether participants in the The residuation method is most appropriate for de-biasing the score of one construct from the influence of contaminating constructs (Dufner, Reitz, & Zander, 2015;John & Robins, 1994;Paulhus, 1998;Plomin, Lichtenstein, Pedersen, McClearn, & Nesselroade, 1990). We de-biased the BTAT-Other Scale's Commandments of Faith subscale by simultaneously regressing scores of that subscale on the Self-Protection Index-Commandments of Faith subscale and on the Indirect Self-Enhancement Index.…”
Section: Commandments Of Faithmentioning
confidence: 99%
“…We tested first whether participants in the The residuation method is most appropriate for de-biasing the score of one construct from the influence of contaminating constructs (Dufner, Reitz, & Zander, 2015;John & Robins, 1994;Paulhus, 1998;Plomin, Lichtenstein, Pedersen, McClearn, & Nesselroade, 1990). We de-biased the BTAT-Other Scale's Commandments of Faith subscale by simultaneously regressing scores of that subscale on the Self-Protection Index-Commandments of Faith subscale and on the Indirect Self-Enhancement Index.…”
Section: Commandments Of Faithmentioning
confidence: 99%
“…In terms of mental well-being, Dufner and colleagues (2012) found that individuals overconfident in their intelligence increased in self-esteem and decreased in depression over the course of eight months, while further work showed that individuals overconfident in their intelligence increased in subjective well-being over the course of nine months (Dufner et al, 2015). However in the study by Robins and Beer (2001), overconfidence predicted decreases in self-esteem over the course of a college career.…”
Section: Longitudinal Studiesmentioning
confidence: 75%
“…In a somewhat different domain, (Dufner, Reitz, & Zander, 2015) found that students who were overconfident in their academic abilities were nominated more frequently for several social roles by classmates. The strongest effects were found when nominating someone they would ask for help or would like to work with, though there were also some positive effects when nominating individuals as friends.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
See 2 more Smart Citations